1978
DOI: 10.1037/0022-006x.46.5.1127
|View full text |Cite
|
Sign up to set email alerts
|

An MMPI scale to separate brain-damaged from functional psychiatric patients in neuropsychiatric settings.

Abstract: An empirical Minnesota Multiphasic Personality Inventory scale was developed to separate brain-damaged from functional psychiatric patients. It consisted of 56 items, which significantly differentiated organic and functional groups in a psychiatric hospital and was named the Psychiatric-Organic (P-O) scale. Upon cross-validation it was found capable of separating organics from process and reactive schizophrenics, alcoholics, and neurotics, as well as patients with character disorders and affective psychoses. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

1981
1981
1989
1989

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…The MMPI forms for all Ss then were scored on eight experimental measures (Hovey, 1964;Russell, 1975;Shaw & Matthews, 1965;Watson, 1971;Watson & Plemel, 1978;Watson & Thomas, 1968) and the Sc scale of the MMPI.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The MMPI forms for all Ss then were scored on eight experimental measures (Hovey, 1964;Russell, 1975;Shaw & Matthews, 1965;Watson, 1971;Watson & Plemel, 1978;Watson & Thomas, 1968) and the Sc scale of the MMPI.…”
Section: Methodsmentioning
confidence: 99%
“…Psychological and/or neurological testing results were screened to insure that a clear diagnosis of organicity or schizophrenia could be made. The MMPI forms for all Ss then were scored on eight experimental measures (Hovey, 1964;Russell, 1975;Shaw & Matthews, 1965;Watson, 1971; Watson & Plemel, 1978;Watson & Thomas, 1968) and the Sc scale of the MMPI.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three of the MMPI special scales have demonstrated particular value in both of these instances. The special scales are the Schizophrenia-Organicity scale (Watson, 1971), the Psychiatric-Organic (P-0) scale (Watson & Plemel, 1978), the Pseudo-Neurological (P-N) scale (Shaw & Matthews, 1965). The Sc-0 scale was developed to differentiate organic from schizophrenic patients and has proved successful in 10 crossvalidation studies (Watson, 1984).…”
mentioning
confidence: 99%
“…As well, the Halperin, Neuringer, Davies, and Goldstein (1977) study failed to differentiate brain-damaged schizophrenics from non-brain-damaged schizophrenics with this measure. An additional scale was developed recently by Watson and Plemel (1978). The Golden et al (1979) crossvalidation found this scale able to discriminate between brain-damaged and normal medical patients who were suffering from backache and neck pain with a hit rate of 90% in the normal sample, but only 57% in the brain-damaged group, achieving an overall classification rate of 73%.…”
mentioning
confidence: 99%